2015
DOI: 10.5114/jcb.2015.54968
|View full text |Cite|
|
Sign up to set email alerts
|

A total EQD 2 greater than 85 Gy for trachea and main bronchus D 2cc being associated with severe late complications after definitive endobronchial brachytherapy

Abstract: PurposeThe endobronchial brachytherapy (EBBT) is an established treatment method for tumors of the tracheobronchial system, however, little is known about the tolerance dose for organ at risk (OAR) in EBBT. The purpose of this study is to analyze patients with superficial bronchial carcinoma treated with definitive EBBT, and to investigate a relationship between late complications and dose for OAR.Material and methodsEndobronchial brachytherapy was performed 6 Gy per fraction for three to four fractions with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Recently, our group investigated the late complication events for patients who underwent endobronchial brachytherapy in our institution [24, 25], and we further extracted a dosimetric parameter, such as D 2 cm 3 in equivalent dose to 2 Gy (EQD 2 ), to reveal a relation between the dosimetric parameters and the late complications rate, as reported by Murakami et al . [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group investigated the late complication events for patients who underwent endobronchial brachytherapy in our institution [24, 25], and we further extracted a dosimetric parameter, such as D 2 cm 3 in equivalent dose to 2 Gy (EQD 2 ), to reveal a relation between the dosimetric parameters and the late complications rate, as reported by Murakami et al . [24].…”
Section: Discussionmentioning
confidence: 99%
“…[24]. As a result, it was discovered that D 2 cm 3  > 85 Gy in EQD 2 for the trachea and the main bronchus is a strong risk factor in relation to severe late respiratory complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although EBB is effective for both alleviating symptoms and eliminating tumors, complications such as hemoptysis, bronchial stenosis and bronchial obstruction remain serious problems [ 14 , 17 25 ]. It has been suggested that these complications can be caused by eccentric locations of the source-delivering catheter in the bronchial lumen [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the reference dose point, it is set at 10 mm from the source axis in most studies [ 9 , 11 , 12 , 17 , 20 , 25 ]. However, the radius of the bronchus is <10 mm on the distal side of main bronchus, and this difference leads to overdosing to the bronchial mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…В 1984 г. W. Schumacher реализовал лазерную реканализацию (ЛР) бронха и эндобронхиальную лучевую терапию (ЭБЛТ) [13,14]. В то же время за последние 20 лет интерес к ЭБЛТ стремительно падает, что находит отражение в уменьшении количества и масштаба публикаций по этой теме [15][16][17][18][19][20][21]. С нашей точки зрения, это может быть связано с новыми возможностями дистанционного способа подведения дозы ионизирующего излучения, которые позволяют исключить инвазивные и трудоемкие брахитерапевтические процедуры в практике лучевого лечения НМРЛ.…”
unclassified